Gaps and overlaps: improving the current regulation of stem cells in the UK. Issue 11 (30th October 2007) - Bell, Leanne; Devaney, Sarah
Abstract : A failure to provide a comprehensive and cohesive regulatory system to govern stem cell research and application will hinder the development of treatments for serious diseases and undermine the UK's attempts to become a global leader in this field